Evaluating Water Delinquency Fees and Financial Assistance Programs Through an Equity Lens. Issue 8 (4th October 2022) - Thompson, Austin; Hackett, Heidi; Bunds, Kyle
Key Takeaways: In 2019, the water utility of Durham, N.C., participated in the National League of Cities' initiative, Cities Addressing Fines and Fees Equitably. Through this initiative, the utility identified inequities in the distribution of cutoffs and delinquency fees across its service area. To address these issues, the utility restructured its social support program, eliminated its 50 delinquency fee, and updated its bill language. Utility reforms to address inequities vary across utilities but include programmatic and policy changes.